Eco- Lodge Patrons’ Characteristics: The Sri Lankan Perspective - Sumanapala, H.D.P.; Perera, P.K.P.; Kotagama, S.W.; Silva, D.A.C.S. (IJRSS, 2015)
As negative environmental and socio-cultural impacts of mass tourism become more apparent, the appeal of alternative forms of tourism, especially ecotourism, has increased globally. With the growing demand for ecotourism and nature-based tourism, eco-lodges are becoming more popular as an alternative accommodation choice. As such, development of eco-lodge industry has wider implications for Sri Lanka, especially when considered the country’s high potential for ecotourism, and the need to provide alternative forms of accommodation for rising tourist arrivals. However, eco-lodge industry is relatively undeveloped in Sri Lanka, and very few or no studies have attempted to explore characteristics of visitors who seek accommodation in eco-lodges. Such knowledge is vital in planning and systematic development of the eco-lodge industry in Sri Lanka. This study attempts to develop distinct visitor profiles of eco-lodge patrons based on their demographic characteristic, trip characteristics and travel motivation. Survey of 220 ecolodge occupants in 12 selected ecolodges found that majority of the respondents were between the ages of 26-55 and, highly educated with at least a bachelor’s degree, and moderate to high income. In terms of trip characteristics, the majority of the respondents stayed in ecolodges for 1-3 days, and travelled with spouse or family. Natural and cultural features were among the main pull motives for selecting the destination. Ecolodge patrons seem rely on the internet, travel guide books, and word of mouth as major sources of information in selecting accommodation. Ecolodge patrons’ strong agreement with statements on nature-based elements, design and service quality indicate that Sri Lankan ecolodges provide unique nature-based experiences for visitors. However, results further indicated that Sri Lankan ecolodge industry has given less attention on the educational or learning component of ecotourism. This calls for better strategies to educate the visitors about their environmental responsibilities, and improved interpretive tour facilities.
Keywords: ecolodge occupants; visitor profiles; trip characteristics; travel motivation; satisfaction